Review of e-commerce legislation harmonization in the Association of Southeast Asian nations (UN New YorkUS, 2013)
Examines legal developments in the areas of e-transactions viz., consumer protection; data protection and privacy; cybercrime; content regulation; domain names and dispute resolution; as well as cloud computing policy.
Keywords: LEGISLATION